Reflections about the activism dissolved on the context of Plante na Praça: colaborative garden in urban environment (Palíndromo, 2020)
Plante na Praça is an artistic action of daily life. This project was liquid, fragmentary, collective, anonymous, finally modifying shared spaces. Because this action was built by various collaborators and has contributed continually to them, it enhances the collective and political action. Everyone involved work towards the same end, the common good of the square. The reflection about the activism of the action allowed approximations between the work of the artist and the ethnographer and also explore the concepts of Political Action and Freedom, by Arendt; Disagreement and Emancipation, by Rancière; becoming, by Deleuze and Guattari; Micropolitics by Guattari and Rolnik; The practice of everyday life and Antidiscipline, by Certeau.
Keywords: site-specific art; collaborative art; urban art; activism